2019
DOI: 10.1634/theoncologist.2018-0587
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Preanalytical Factors and Tumor Mutational Burden Estimated by Next-Generation Sequencing-Based Multiplex Gene Panel Assay

Abstract: Background Tumor mutational burden (TMB) measured via next‐generation sequencing (NGS)‐based gene panel is a promising biomarker for response to immune checkpoint inhibitors (ICIs) in solid tumors. However, little is known about the preanalytical factors that can affect the TMB score. Materials and Methods Data of 199 patients with solid tumors who underwent multiplex NGS gene panel (OncoPrime), which was commercially provided by a Clinical Laboratory Improvement Amendments‐licensed laboratory and covered 0.78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Firstly, we have to take into account inter‐sample differences given the groups of untreated, UDG‐treated FFPE and FF DNA samples were not extracted from the same tumours. In addition, DNA integrity is inversely proportional to the duration of tissue fixation 33 . Because our study included archival material processed during routine care, we cannot confidently reconstruct the influence of fixation on DNA quality.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we have to take into account inter‐sample differences given the groups of untreated, UDG‐treated FFPE and FF DNA samples were not extracted from the same tumours. In addition, DNA integrity is inversely proportional to the duration of tissue fixation 33 . Because our study included archival material processed during routine care, we cannot confidently reconstruct the influence of fixation on DNA quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method is challenging to adopt in daily clinical practice, due to high costs and long turnaround times. As a consequence, an increasing number of studies has tried to demonstrate whether targeted NGS gene panels might determine TMB with reliable precision [15,[18][19][20]. While initial studies have shown that targeted NGS gene panels offer reliable estimates of TMB, substantial concerns regarding the stochastic error associated to limited gene panel sequencing have been raised [15,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these factors can impact TMB reproducibility, even when using the same assay [8]. Another significant issue is represented by the lack of standardization of the genes of interest, which can vary greatly among commercial and custom panels [3,11,12,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum input DNA quantity required for creating libraries was 150 ng per sample, while the median depth of coverage was more than 3000. Variant calling software VarPROWL (r20278) was used for variant calling [ 13 ].…”
Section: Methodsmentioning
confidence: 99%